PENERAPAN INOVASI DATA DAN TEKNOLOGI DIGITAL DALAM PENGELOLAAN DISIPLIN SISWA DAN ABSENSI PEGAWAI DI LEMBAGA PENDIDIKAN - Naufal, Naifi; Lubis, Moh. Anshory; Ahmadi, Indra Saputra (FIP UNIRA MALANG, 2025)
This community service program aims to enhance the effectiveness of educational administration management through the application of data innovation and digital technology. The activities were carried out by utilizing the outcomes of student internships from the Data Science Study Program, Universitas Insan Cita Indonesia, at two partner educational institutions. First, at SMK Putra Bangsa Waru Pamekasan, students developed a more structured and automated Microsoft Excel-based system for recording student disciplinary points. Second, at Pondok Pesantren As-Sunnah Lombok, students designed an integrated employee attendance system using web technology (Laravel & Livewire) and mobile applications (Flutter) with GPS and QR Code features. The results show that digitalization not only simplifies data recording and recapitulation but also fosters a culture of discipline and administrative transparency. These findings are consistent with the literature, which highlights that the use of digital technology in educational management improves efficiency, accuracy, and accountability.